Analysis of Smear Microscopy and Culture Conversion Results in Multidrug-Resistant Tuberculosis Patients with and without Type 2 Diabetes Mellitus - Henny Fauziah; Aprianti S; Handayani I; Kadir NA (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
The World Health Organization (WHO) recommended microscopic AFB smear examination and culture as follow-ups to the response of MDR TB therapy. Analyzed the results of microscopic AFB smear and culture conversion as well as treatment outcome in Multidrug-Resistant Tuberculosis (MDR-TB) patients with and without Diabetes Mellitus (DM). This is a retrospective study involved 70 MDR-TB patients with (27 patients) with DM and without DM (43 patients) who had microscopic AFB smear and culture results at the start of the follow-up therapy. This research was conducted at Labuang Baji Regional Public Hospital, Makassar, from June to July 2019, used medical records of MDR-TB patients the period of June 2016 to December 2017. The results showed that 52 out of 70 MDR-TB patients had microscopic AFB smear and culture conversion in MDR-TB with DM (21 patients) and without DM (31 patients). The duration of microscopic AFB smear conversion in MDR TB patients with DM (3.33±0.54 months) was longer than patients without DM (2.07±0.05 months), p=0.001. While in culture conversion, there was no significant difference between MDR-TB with DM (1.28±0.64 months) and without DM (1.25±0.59), p=0.648. The recovery outcome between MDR-TB with (48.1%) and without DM (48.8%) was not significantly different. However, the output of treatment failure was greater in DM (11.2%) than without DM (2.3%), although statistically, there was no significant difference (p=0.568). Multidrug-resistant tuberculosis patients with DM experienced slower microscopic AFB smear conversion than MDR-TB patients without DM. However, in culture, there was no significant difference in the conversion period between the two groups. MDR-TB patients, both of with and without DM, had the same chance of recovery.